IMPLEMENTASI METODE (PBL) PEMBELAJARAN PAI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA SDN 21 KOTA BIMA - Sukiani; Ade Nurfadillah; Nasaruddin (STKIP Subang, 2025)
This study aims to investigate in depth the impact of the implementation of the Problem Based Learning (PBL) method on student learning motivation at SDN 21 Kota Bima. The methodology used in this study is qualitative, applied to understand the experiences experienced by students and teachers during the learning process, as well as to identify elements that can support or hinder the success of the implementation of PBL. By collecting data through classroom observations, interviews with teachers, and discussions with students, from the results of the study at SDN 21 KOTA BIMA, the (PBL) method has been implemented and the reason why teachers apply the problem-based learning (PBL) method is so that students can think critically and solve problems and prepare themselves for future life, in addition to training students to find solutions to problems they face in their lives. Based on interview and observation data, the PBL method can increase student learning motivation, based on the results of eight interviews, involving five students and three teachers. Of the eight interviewees, only two said the PBL method was boring and somewhat difficult, while the other five said the method was fun and not boring, and also increased student engagement. They were very enthusiastic and actively raised their hands when asked questions related to their real lives by the teacher. Based on interview and observation data, the PBL method can increase student learning motivation, based on the results of eight interviews, involving five students and three teachers. Of the eight interviewees, only two said the PBL method was boring and somewhat difficult, while the other five said the method was fun and not boring, and also increased student engagement. They were very enthusiastic and actively raised their hands when asked questions related to their real lives by the teacher.